Triclocarban and Triclosan Inhibit Human Aromatase via Different Mechanisms. - Li, Huitao; Zhao, Yu; Chen, Lanlan; Su, Ying; Li, Xiaoheng; Jin, Lixu; Ge, Ren-Shan (BioMed Research International, 2017)
Human aromatase (CYP19A1) is an important enzyme, which produces estrogen from androgen for maintaining the female reproductive function and pregnancy. Triclocarban and triclosan are antimicrobial chemicals added to personal care, household, and industrial products. They could be endocrine disruptors and may disrupt human CYP19A1 activity. In the present study, we investigated the effects of triclocarban and triclosan on estradiol production and human CYP19A1 activity in JEG-3 cells. Triclocarban and triclosan reduced estradiol production in JEG-3 cells. Triclocarban and triclosan inhibited human CYP19A1 with IC50 values of 15.81 and 6.26 μM, respectively. Triclosan competitively inhibited CYP19A1, while triclocarban noncompetitively inhibited this enzyme. Docking study showed that triclosan bound to the steroid-binding pocket of CYP19A1, while triclocarban was off this target, suggesting a different mechanism. In conclusion, triclocarban and triclosan are inhibitors of human CYP19A1.